Ecoando dos cinco cantos: feminismo negro brasileiro e questões de direitos humanos - Castro, Ana Luísa Machado de (2018)
This dissertation investigates the relations between Brazilian Black Feminism and Human Rights violation/effectiveness processes, based on data received in seven interviews with Brazilian black women from all regions of the country. Focusing in the experience of black women, we expect to enlarge reflections on human rights to empower this tool to promote social justice and confront inequalities. The dissertation is divided in three chapters, in addition to the introduction and final considerations. The first chapter presents a reflection on the hegemonic field of human rights studies, seeking to problematize its main assumptions. Using decolonial theory, we discuss the history of human rights in modernity e use of the modern rights, the idea of human and un-human and about multiple human rights violations of black women. In the second chapter, we will characterize Brazilian black feminism and its participation in processes that involve violation/effectiveness of human rights in the country. We will address to some important milestones of the struggle of Brazilian black women, the relations with feminist and black movements and some theoretical formulations that emerge from these contexts. Finally, in the third chapter, we analyses the voices of the research collaborators. We present the point of view of theses black women on black feminism and human rights violation/effectiveness.